Alpha – particle confinement control and Alfven wave-particle interaction - Shishkin, A.A.; Shishkin, O.A. (Вопросы атомной науки и техники, 2000)
Two important physics effects are found in the interaction of the particle with the electromagnetic field of Alfven type wave in the toroidal magnetic trap: the increase/decrease of the radial deviation of the particle under the effect of the switching on/off of the time dependent part of the electromagnetic perturbation.